KEBIJAKAN FORMULASI HUKUM PIDANA DALAM MELANGGULAGI KEJAHATAN SKIMMING ATM - Erwin Ubwarin (SASI, 2015)
Advances in technology and science make people no longer have to go to the bank to make a transaction, one example of progress is the Automatic Teller Machine (ATM), we do not need to go to a bank teller for transactions, but the progress is also not free from crime skimming ATM data victims were taken without the knowledge of the victim then copy the bulging ATM card. after that the account balance is drained until the end, if a crime is allowed it will disrupt the economy of the State, the customer no longer wants to save money so that this act should be criminalized so that the legal basis in law enforcement.